2013
DOI: 10.4209/aaqr.2012.06.0152
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring PM10 and Ultrafine Particles in Urban Environments Using Mobile Measurements

Abstract: Mobile platforms are increasingly used to acquire air quality data at a high spatial and temporal resolution in complex urban environments. As such, mobile measurements provide a solution for short-term studies to acquire a spatially spread data set that would not be feasible if using stationary measurements. Mobile monitoring campaigns were carried out with a bicycle platform at two different urban locations, consisting of 20 and 24 repeated runs along a fixed route over a threeweek period. The measurement ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 42 publications
2
57
0
8
Order By: Relevance
“…It can provide insight into the spatial variability that would not be possible with stationary monitors. Previous case studies already showed the potential of repeated mobile measurements for the assessment of spatial variability of pollutants at different micro-environments in a city at street level Peters et al, 2013) and within street-level (Zwack et al, 2011b;Peters et al, 2014).…”
Section: Mobile Monitoring To Assess Spatial Variationmentioning
confidence: 99%
See 3 more Smart Citations
“…It can provide insight into the spatial variability that would not be possible with stationary monitors. Previous case studies already showed the potential of repeated mobile measurements for the assessment of spatial variability of pollutants at different micro-environments in a city at street level Peters et al, 2013) and within street-level (Zwack et al, 2011b;Peters et al, 2014).…”
Section: Mobile Monitoring To Assess Spatial Variationmentioning
confidence: 99%
“…For one experiment, the procedure explained above is repeated a high number of times (1000 iterations, where each iteration is one random combination of the runs) to minimize the influence of random effects. This data experiment is based on the work of Peters et al (2013), but differs from it in the application of a random selection with replacement instead of without replacement. When using random selection without replacement (each run can only be selected once), the average would converge exactly to the overall average when more runs are added and convergence would always be obtained.…”
Section: Data Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts with targeted mobile monitoring, which is a coordinated, goal-driven approach in which the mobile measurements are deliberately planned and carried out with a specific purpose in mind (see e.g. case studies described in Peters et al (2013), Peters et al (2014) and Van den Bossche et al (2015)). Opportunistic mobile monitoring is a promising approach to collect large data sets that give useful additional information at a reasonable cost compared to classical data collection methods.…”
Section: Opportunistic Mobile Monitoringmentioning
confidence: 99%